EFEKTIFITAS DAN KONTRIBUSI DANA PENDIDIKAN ACEH: Studi Kasus Program Beasiswa Aceh - Arfiansyah Arfiansyah (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2017)
Educational scholarships have long been disbursed by the Aceh Government for Aceh people to undertake undergraduate, graduate and doctoral programs in Indonesia or abroad. However, research to determine the effectiveness of the Aceh Scholarship and the contribution of the fund has not been done. This study examines the extent of effectiveness of Aceh's scholarship management and the contribution of recipients to Aceh's development. For this purpose, interviews with a number of stakeholders involved, such as fund managers and scholarship recipients and managers, and document analyses were conducted. The results show that while there are still many problems, LPSDM has made a number of breakthroughs to help students to study at a number of universities using Acehnese scholarships. Furthermore, the alumni have also contributed greatly to Aceh, especially through the institutions where they work.